SoftwIre Integration - An Onto-Neural Perspective - Ludolph, Hendrik; Kropf, Peter; Babin, Gilbert (: Springer, 2011)
We propose a framework for automated point-to-point application integration. Functional and technical aspects to consider are presented. We advocate using intelligible (ontological) and distributed (neural networks) knowledge representations to guide design and implementation of application interfaces. We believe this yields benefits over manual approaches currently used, in which business specifications are first captured, then translated into technical specifications, and finally implemented, often by costly third-party integration specialists. The present work initiates research efforts towards automation of the latter two activities, with a potential impact on professional-services costs and time-to-operation.
, 2011
Keywords: ontology matching; neural network; application integration